The Value of the Catholic Faith in God through the Devotion to the Statue of Saint Anthony: Case Study of the Church of Saint Anthony, Don Mottanoi, Ratchaburi Diocese - Amnatkiattikul, Watcharapon; Saengthien, Pichet; Chumsriphan, Surachai; Prasootsaengchan, Laddawan (Saengtham College Journal, 2026)
This research aimed to study: 1) the value of the Catholic faith in God through the devotion to the statue of Saint Anthony by considering this devotion in the context of the church of Saint Anthony, Don Mottanoi, Ratchaburi Diocese. 2) Guidelines to increase the faith of Christians in God through the devotion to the statue of Saint Anthony. Case study of the church of Saint Anthony, Don Mottanoi, Ratchaburi Diocese. The informants consisted of 15 Christians of Saint Anthony’s Church and devotees who come to pay respect and seek blessings from the statue of Saint Anthony, as well as 9 experts. The research instruments included two sets of semi-structured interview forms. The data were analyzed using frequency, percentage, and content analysis for the interview data. The results of this study were: The value of Catholic faith through this devotion is rooted in a profound relationship with God, characterized by imploring divine grace across various existential dimensions, including family well-being, health, the recovery of lost items, academic pursuits, military conscription, fertility, career stability, safe travels, and divine providence through saintly intercession. Values that Christians receive from learning about Saint Anthony’s virtues include spiritual values and values in promoting theological virtues, namely, of faith, hope, and love. Examples that Christians receive from learning the saint’s biography include the virtue of courage in proclaiming Christianity to those of other faith, as well as humility and simplicity, so characteristic of Saint Anthony. Guidelines to increase the Catholic faith in God of Christians through the devotion to Saint Anthony are as follows: 2.1 There should be instruction on the teaching of the Church regarding the devotion to Saint Anthony. 2.2 There should be an explanation of life, examples and virtues of Saint Anthony. 2.3 There should be modern ways of communication, like creating a website, putting up posters, and disseminating digital media to foster the faith and devotion to God through Saint Anthony. 2.4 There should be an explanation about the local traditions of making vows or using firecrackers so that the faithful and members of other religions understand their meaning. 2.5 To increase the faith, there should be a distribution of leaflets with the Word of God or the teachings of Saint Anthony after the novena Mass of the Saint every month. 2.6 The priest presiding the novena should preach about Saint Anthony so that people may be able to follow his examples. 2.7 The church should establish a youth group devoted to the saint and organize activities that foster the faith. 2.8 The school should explain and organize activities with the students about life, examples and virtues of Saint Anthony.